Possible Causes of Extremely Warm Early Summer in North China During Cold and Warm Periods - Li, Xiaofan; Yao, Zhiping; Wang, Xiaojuan; Yu, Changwen; Che, Shaojing; Gong, Zhiqiang; Feng, Guolin; Li, Tianyu (Frontiers in Climate, 2021)
The abnormal characteristics of extremely warm early summer (EWES) in the North China under different decadal background were contrastively analyzed. Their relationships with upper-and-lower-level atmospheric circulation and global sea surface temperature anomalies (SSTAs) were also discussed. Results show that temperature anomalies of EWES in the North China are overall higher than normal in both cold (1961-1993) and warm (1994-2019) periods, but the anomalies of the latter are much higher than that of the former. EWES in the North China is directly related to the circulation lying between 40°— 50°N in the middle troposphere, which lead to positive temperature anomalies occurring from the bottom to the upper level of the troposphere together with a high anomaly trend tilting northward. The persistent and strong Eurasian continental high (ECH), weak Northeast China cold vortex (NECV) activity, together with the strong western Pacific subtropical high (WPSH) are major factors that directly lead to the EWES in North China. ECH and WPSH are stronger and larger, and NECV are weaker and more northward in the warm period than in the cold period. In addition, the positive SSTAs in the tropical Indian Ocean and the Kuroshio area are favorable for the stronger and larger ECH and WPSH, as well as the weaker and more northward NECV, causing strong anticyclonic and downward circulation system controlling the North China, resulting in the extremely warm temperature there. The joint impact of the positive tropical Indian Ocean SSTAs and the Kuroshio region SSTAs is more significant during warm period than cold period, resulting in much stronger EWES in the North China during warm period.